Belonging and Becoming: Voices of Harmonious Being. Young Women Steiner Students Explore Their Lifeworlds Through Goethean Conversation - Lambert, Althea Louise (Auckland University of Technology, 2012)
There are two central strands to this study, the voice of Steiner (or 'Waldorf') education and the voice of young women - voices rarely heard in the mainstream educational arena. Together they are the voice of 'harmonious being', a phrase which I have used to describe the phenomenon of the Steiner education experience which aims for harmonisation of the whole human being. Who the young person becomes is central to this experience yet there is little in-depth research exploring the Steiner student's voice. By addressing this gap and inviting young women Steiner students to explore this phenomenon through conversation this study achieves three significant visions. First, it raises the social voice of young women and challenges the negative stereotype of 'adolescent girl' proffered by the media. Second, it illuminates the living experience of an educational initiative that fosters connectedness and humankind's spiritual wisdom. Third, it demonstrates the value of simply talking and 'listening with spirit' to stay present in conversation and 'experience the other' through empowered and heart-centred relationships. As a consequence of doing this research, a fourth vision has emerged showing the value of love as methodology. Over one school year (9 months) I met regularly with twelve young women secondary students (14-18 years of age) from a New Zealand Steiner school to explore the phenomenon of harmonious being through conversations about their lives. Our conversations advance an intuitive methodology of love, connectedness and wholeness, which is encapsulated in a new methodological mix combining Goethean phenomenology with Carol Gilligan's relational psychology. Together they invoke the recognition of our innate connectedness. Goethe's is an artistic science of withness and wholeness ('one voice resonates with all voices') focusing on the epiphany experience of the archetypal phenomenon. Gilligan's voice-centred relational psychology has provided a humanistic feminist lens through which women and men come together as 'human' as heard in the layers of conversations with these young women. In this study, epiphany moments were unfolded in detail in six conversations series through a four stage process of Goethean layered listening. The themes of 'Belonging and Becoming' that emerged were explored through the collective voices of the twelve young women. The young women in this study offer insightful and rare views of their lifeworlds; voices rich with wisdom constructing 'adolescence' as a time of creative development. These young women show a remarkable interest in the world and a keen awareness of their social, cultural and physical environments locally, nationally and internationally. As evocative social agents they recreate the conventional 'moody adolescent' to a meaningful picture of what matters to a young woman as she authors her own life. What Gilligan calls 'the voice of resistance' is alive and well in these young women. Their experiences of 'harmonious being' transcribe a fluid lemniscate path of discovery between voice as self and their world-relationships: a structure with ribbon, says Laura. They describe an awakening to 'who they are' as a 'self-belonging', which creates space to become and belong more fully to 'who they will be'. Through the voices of young women Steiner students this study tells that the living spirit of Steiner education is alive and well in the 21st Century. This research became the very experience of the phenomenon we were exploring, unfolding a natural human science that has shifted the voice of phenomenology from 'lived' to 'living' experience and revealed a relational methodology of an embodied dynamic voice, epitomised in the phrase: belonging and becoming.
Keywords: Steiner education; Goethean conversation; Young women; Relational psychology; Adolescence; Voice; Harmonious being; Belonging; Love connectedness wholeness; Natural human science